2022
DOI: 10.1186/s12884-022-04549-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, associated factors and perinatal outcomes of antepartum depression in Ibadan Nigeria

Abstract: Background Antepartum depression is the most common mental health disorder in pregnancy and it is also a risk factor for adverse perinatal outcomes. Low and middle income countries like Nigeria bear a higher burden of antepartum depression compared with high income countries. Prioritizing mental health issues among pregnant women is crucial to achieving the Sustainable Development Goals. We determined the prevalence, associated factors and perinatal outcomes of antepartum depression among pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
16
0
2
Order By: Relevance
“…Additionally, we found that a history of induced abortion increased the likelihood of CEATU by fivefold compared with women without a similar history. Studies have reported that a history of induced abortion and other high-risk behaviours increases the risk of depression among pregnant women and, consequently, prenatal substance use [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that a history of induced abortion increased the likelihood of CEATU by fivefold compared with women without a similar history. Studies have reported that a history of induced abortion and other high-risk behaviours increases the risk of depression among pregnant women and, consequently, prenatal substance use [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the fact. It has been postulated that fetal growth prior to 20-week gestation is predominantly determined by genetic predisposition whereas growth in the third trimester is more likely determined by the intra uterine environment [2]. Maternal distress is reported not to be related to a decrease in estimated fetal weight before the third trimester but all types of maternal distress were negatively associated with fetal weight in late pregnancy [2].…”
Section: Discussionmentioning
confidence: 98%
“…Depression as an illness is known to occur at different phases of the reproductive cycle (premenstrual dysphoric disorder, depression in pregnancy and postpartum depression) [1]. Antenatal (prenatal or antepartum) depression is a nonpsychotic depressive episode that begins during pregnancy and it is the commonest mental health disorder in pregnancy [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Documenting prevalence was a primary objective in a number of the Collection papers [31][32][33], particularly in low and middle income country settings. Where factors were identified which predict poorer perinatal mental health, these were commonly associated with disadvantage and limited access to resources.…”
Section: Incidence Determinants and Factors Associated With Poor And ...mentioning
confidence: 99%